Association between Serum Phosphorus Levels and Diabetic Retinopathy: A Cross-Sectional Study - Jintao Chen; Chuanfeng Liu; Cunwei Sun; Jia Zeng; Jingwei Chi; Kui Che; Yangang Wang (International Journal of Endocrinology)
Background and Aims. The aim of this study was to investigate the association between serum phosphate levels and diabetic retinopathy (DR) in patients with type 2 diabetes mellitus (T2DM). Methods and Results. The study sample consisted of 1657 T2DM patients hospitalized between 2017 and 2019. Patients were categorized into quartiles based on their serum phosphate levels (Q1–Q4). An increasing trend in the prevalence of DR was observed across these quartiles. Subsequently, logistic regression analysis was employed to adjust for potential confounders, such as gender, age, BMI, and duration of diabetes, and to evaluate the odds ratios (ORs) associated with these quartiles. The prevalence of DR showed an increasing trend with elevated serum phosphate levels. Logistic regression further confirmed that serum phosphate levels remain an independent risk factor for DR. Conclusion. Elevated serum phosphate levels are closely associated with the prevalence of DR in hospitalized T2DM patients. Further studies are needed to establish causality. This trial is registered with chiCTR2000032374.